A novel intranasal breath-powered delivery system for sumatriptan: a review of technology and clinical application of the investigational product AVP-825 in the treatment of migraine. (September 2015) - Cady, Roger
<x xml:space="preserve">Abstract</x> Introduction: AVP-825, formerly 'OptiNose Sumatriptan, ' is an investigational Breath-PoweredTM Bi-DirectionalTM intranasal delivery system containing low-dose sumatriptan (22 mg intranasal powder) that avoids limitations of other types of intranasal administration by taking advantage of unique features of nasal anatomy and physiology. Areas covered: This review summarizes intranasal drug delivery for migraine, how the breath-powered technology works, and AVP-825 pharmacokinetic, efficacy and safety/tolerability findings. To identify AVP-825 clinical studies, a PubMed/MEDLINE database search was conducted with the terms AVP-825, OptiNose, OptiNose Sumatriptan, Breath-Powered Nasal Delivery or sumatriptan powder. Of 20 articles, 5 clinical studies were identified, including the head-to-head comparative COMPASS trial (AVP-825 vs oral sumatriptan) and two placebo-controlled studies. Expert opinion: AVP-825 has faster sumatriptan absorption versus oral tablets or traditional liquid nasal spray. In Phase II/III randomized, double-blind, placebo-controlled trials, AVP-825 produced early and sustained efficacy with minimal triptan-related adverse effects. In COMPASS, AVP-825 produced earlier reduction of migraine pain intensity and migraine-associated symptoms than 100 mg oral sumatriptan, and higher early rates of pain relief and pain freedom, similar sustained efficacy, and fewer atypical sensations. AVP-825 has the potential to provide migraine patients with improved intranasal administration of sumatriptan that may enhance efficacy and tolerability.